2010
DOI: 10.3899/jrheum.100069
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Adalimumab in Patients with Active Psoriatic Arthritis Who Have Not Adequately Responded to Prior Therapy: Effectiveness and Safety Results From an Open-label Study

Abstract: Objective.To evaluate the effectiveness and safety of adalimumab in patients with active psoriatic arthritis (PsA) and an inadequate response to prior therapy.Methods.Patients were treated with subcutaneous injections of adalimumab 40 mg every other week in addition to their standard antirheumatic therapies in a 12-week, open-label study. Effectiveness evaluations at Week 12 included American College of Rheumatology (ACR) and Psoriasis Area and Severity Index (PASI) response rates, Psoriatic Arthritis Response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 16 publications
1
31
1
6
Order By: Relevance
“…Some studies used a simple count of dactylitic digits (based on clinician opinion), while others graded the severity 0-3 or 1-4, and all 20 digits were Because of the large variability in study designs and outcome measures, and poor availability of primary data, a metaanalysis could not be performed. Significant improvement (p < 0.05) in dactylitis compared to placebo was observed with the use of certolizumab in the RAPID-PsA trial 4 and with ustekinumab in the PSUMMIT1 trial 6 ; in Phase II studies, with the use of golimumab in the GO-REVEAL trials 8,9 ; with infliximab in the IMPACT1 21 and IMPACT2 22 trials; with a combination of infliximab plus methotrexate compared to methotrexate alone in an open-label study 11 ; and with the use of adalimumab in prior treatment failures in other open-label studies 7,15 .…”
Section: Journal Of Rheumatologymentioning
confidence: 88%
See 1 more Smart Citation
“…Some studies used a simple count of dactylitic digits (based on clinician opinion), while others graded the severity 0-3 or 1-4, and all 20 digits were Because of the large variability in study designs and outcome measures, and poor availability of primary data, a metaanalysis could not be performed. Significant improvement (p < 0.05) in dactylitis compared to placebo was observed with the use of certolizumab in the RAPID-PsA trial 4 and with ustekinumab in the PSUMMIT1 trial 6 ; in Phase II studies, with the use of golimumab in the GO-REVEAL trials 8,9 ; with infliximab in the IMPACT1 21 and IMPACT2 22 trials; with a combination of infliximab plus methotrexate compared to methotrexate alone in an open-label study 11 ; and with the use of adalimumab in prior treatment failures in other open-label studies 7,15 .…”
Section: Journal Of Rheumatologymentioning
confidence: 88%
“…Only randomized, double-blind placebo-controlled (RCT) or open-label trials of PsA in which dactylitis was assessed as a separate outcome measure were identified. Thus, 74 articles (English-language reports only) were identified, and 29 articles were selected for full review [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]25,26,27,28,29,30,31 .…”
mentioning
confidence: 99%
“…As treatment with a DMARD can lead to the improvement of QoL,47 the positive effects of early treatment may extend beyond the clinical outcomes.…”
Section: Addressing the Challenges To The Effective Management Of Psamentioning
confidence: 99%
“…A Canadian open-label study to evaluate the safety and effectiveness of adalimumab when added to inadequate therapy for the treatment of PsA (ACCLAIM) enrolled 127 PsA patients who received 40 mg adalimumab every other week, in addition to pre-existing PsA treatment, for 12 weeks [73]. A decrease in the proportion of patients with enthesitis was observed during the study: tenderness of the Achilles tendon reduced from 30% of patients to 14% (p = 0.004), and tenderness of the plantar fascia from 24 to 11% (p = 0.008).…”
Section: Treatment Of Enthesitis In Psoriatic Arthritismentioning
confidence: 99%